Certain aspects relating to the taxation of collective investment schemes in South Africa - Truswell, Stewart (Department of Commercial Law, 2024)
[pg 24 is missing] This paper examines certain aspects of the taxation relating to collective investment schemes (sometimes referred to- both generally and in this paper- as unit trusts), particularly equity collective investment schemes structured as trusts.